2009
DOI: 10.1111/j.1468-2982.2009.01986.x
|View full text |Cite
|
Sign up to set email alerts
|

Intact neurovascular coupling during executive function in migraine without aura: Interictal near-infrared spectroscopy study

Abstract: An altered neurovascular coupling has been proposed in migraine. We aimed to investigate neurovascular coupling during a mental task interictally in patients with migraine without aura (MO) by near-infrared spectroscopy (NIRS). Twelve migraineurs and 12 healthy controls were included. Using NIRS, we recorded the magnitude and latency of cortical changes in oxyhaemoglobin (HbO(2)) and deoxyhaemoglobin (Hb) during the colour-word matching Stroop test via 16 channels covering the forehead. We found no differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 66 publications
(101 reference statements)
4
17
0
Order By: Relevance
“…Given that the stop signal reaction time (SSRT) provides an effective means of quantifying the latency of the inhibition mechanism, the slower SSRT implied a decrease or disruption in response inhibition in migraineurs. Such poorer performance during a stop signal task is in line with previous studies reporting that migraineurs during the interictal period relative to healthy controls showed signi cantly slower RTs on incongruent trials during the Stroop interference test without a between-group difference in commited errors (37,48). Given that the Stroop interference test measured cognitive interference or inhibition (26), the behavioral nding in the present study indicates that the impairment in inhibitory control in migraineurs can occur not only during the early and intermediate stage of information processing, but also during the late stage of information processing, such as response execution.…”
Section: Discussionsupporting
confidence: 90%
“…Given that the stop signal reaction time (SSRT) provides an effective means of quantifying the latency of the inhibition mechanism, the slower SSRT implied a decrease or disruption in response inhibition in migraineurs. Such poorer performance during a stop signal task is in line with previous studies reporting that migraineurs during the interictal period relative to healthy controls showed signi cantly slower RTs on incongruent trials during the Stroop interference test without a between-group difference in commited errors (37,48). Given that the Stroop interference test measured cognitive interference or inhibition (26), the behavioral nding in the present study indicates that the impairment in inhibitory control in migraineurs can occur not only during the early and intermediate stage of information processing, but also during the late stage of information processing, such as response execution.…”
Section: Discussionsupporting
confidence: 90%
“…FNIRS detects the changes in light absorption and scattering in tissue caused by changes in concentration of oxyhemoglobin (∆HbO) and deoxyhemoglobin (∆Hb) secondary to neuronal activity, through a neurovascular coupling mechanism that is currently under investigation [17]. Though fNIRS can measure the slow hemodynamic response elicited by neuronal activity that correlates with corresponding fMRI measurements [5], it is often the case that the activation signal-to-noise ratio (SNR) in fNIRS is low due to poor optical contact between the optical fibers that deliver and collect near infrared (NIR) light to and from the scalp [18].…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48] fNIRS detects changes in light absorption and scattering in tissue caused by fluctuations in oxy-hemoglobin (HbO) and deoxyhemoglobin (Hb) concentrations secondary to neuronal activity, known as neurovascular coupling. 49,50 It has also been shown that fNIRS is able to detect event-related optical signals, which occur within hundreds of milliseconds and correlate with evoked potentials measured by simultaneous electroencephalography (EEG), 51,52 are much faster than the seconds resolution of fMRI. 53,54 Recently, fNIRS detected changes in resting state HbO after anodal tDCS was applied to the prefrontal cortex, 55 though no fNIRS studies to date have explored the effects of tDCS on functional activation patterns in the sensorimotor cortex, which is the focus of this work.…”
mentioning
confidence: 99%